Network pharmacology-based study to investigate the mechanism of compound houttuynia mixture against influenza virus infection by suppressing TLR7/MyD88 signaling pathway - Hailin Wei; Wenlei Wang; Qin Su; Zhihui Zheng; Zihan Chen; Xinyue Zhang; Yihan Xu; Xiaoquan Wang; Pinghu Zhang (Journal of Traditional and Complementary Medicine)
Aim of the study: Compound houttuynia mixture (CHM) has been approved to cure respiratory diseases in China. However, the anti-influenza virus effect and underlying mechanism of CHM remains to be confirmed. Materials and methods: The in vitro activity of CHM against H3N2 virus was evaluated using MDCK, A549 and THP-1 cells as an in vitro model. The in vivo protective effect on H3N2 virus infection was investigated. Moreover, serum cytokines were measured with high throughput liquid phase protein chip. The anti-influenza mechanism of CHM was predicted by network pharmacology and further validated with immunoblotting. Results: Our results indicated that CHM has significant inhibitory effect on the replication of influenza A H3N2 virus. Furthermore, CHM could effectively reduce the mortality caused by lethal H3N2 virus infection by prolonging the survival time, reducing lung pathological injury, and suppressing excessive cytokines storm. Network pharmacology revealed that the protective effect of CHM on influenza virus infection was involved in multiple targets and multiple pathways. Mechanistic validation indicated that inhibiting the excessive activation of TLR7/MyD88 signaling pathway may be the critical mechanism of CHM exerting the protective effect against influenza virus infection. Conclusion: Regulating of TLR7/MyD88/NF-κB signaling pathway in multiple target cells might be one of key mechanisms of CHM by inhibiting virus replication and excessive inflammatory. Our findings indicated that CHM might be an effective treatment for influenza virus infection.